Correlation of Clinical Neuromusculoskeletal and Central Somatosensory Performance: Variability in Controls and Patients With Severe and Mild Focal Hand Dystonia. Issue 3 (2002) - Byl, Nancy N.; Nagarajan, Srikantan S.; Merzenich, Michael M.; Roberts, Tim; McKenzie, Alison
Abstract : Focal hand dystonia (FHd) is a recalcitrant, disabling movement disorder, characterized by involuntary co-contractions of agonists and antagonists, that can develop in patients who overuse or misuse their hands. The aim of this study was to document clinical neuromusculoskeletal performance and somatosensory responses (magnetoencephalography) in healthy controls and in FHd subjects with mild versus severe hand dystonia. The performance of healthy subjects (n = 17) was significantly better than that of FHd subjects (n = 17) on all clinical parameters. Those with mild dystonia (n = 10) demonstrated better musculoskeletal skills, task-specific motor performance, and sensory discrimination, but the performance of sensory and fine motor tasks was slower than that of patients with severe dystonia . In terms of somatosensory evoked field responses (SEFs), FHd subjects demonstrated a significant difference in the location of the hand representation on the x and y axes, lower amplitude of SEFs integrated across latency, and a higher ratio of mean SEF amplitude to latency than the controls. Bilaterally, . those with FHd ( mild and severe ) lacked progressive sequencing of the digits from inferior to superior. On the affected digits, subjects with severe dystonia had a significantly higher ratio of SEF amplitude to latency and a significantly smaller mean volume of the cortical hand representation than those with mild dystonia . Severity of dystonia positively correlated with the ratio of SEF mean amplitude to latency (0.9029 affected, 0.8477 unaffected; p< 0.01 ). The results of the present study strengthen the evidence that patients with FHd demonstrate signs of somatosensory degradation of the hand that correlates with clinical sensorimotor dysfunction, with characteristics of the dedifferentiation varying by the severity of hand dystonia. If these findings represent aberrant learning, then effective rehabilitation must incorporate the principles of neuroplasticity. Training must be individualized to each patient to rebalance the sensorimotor feedback loop and to restore normal fine motor control.